2016
DOI: 10.1007/978-4-431-55982-5
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Resilience of Education Systems

Abstract: Scope of the SeriesDisaster risk reduction is a process, which leads to the safety of community and nations. After the 2005 World Conference on Disaster Reduction, held in Kobe, Japan, the Hyogo Framework for Action [HFA] was adopted as a framework of risk reduction. The academic research and higher education in disaster risk reduction has made and is making the gradual shift from pure basic research to applied, implementation-oriented research. More emphasis is given on the multi-stakeholder collaboration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 23 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…Moreover, several categories emerged when evaluating the disaster-related content of the activities and programs as these were shown in Table 2. The content of the activities and programs from the studies were aligned with the suggested guidelines for disaster education content (Shaw et al, 2011;Bahandari, 2014;Shiwaku et al, 2016). Additionally, one of the studies (Sharpe & Izadkhah, 2014) included the concept of caring for pets during earthquakes as a part of their educational content.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Moreover, several categories emerged when evaluating the disaster-related content of the activities and programs as these were shown in Table 2. The content of the activities and programs from the studies were aligned with the suggested guidelines for disaster education content (Shaw et al, 2011;Bahandari, 2014;Shiwaku et al, 2016). Additionally, one of the studies (Sharpe & Izadkhah, 2014) included the concept of caring for pets during earthquakes as a part of their educational content.…”
Section: Conclusion and Discussionmentioning
confidence: 99%